Absolute dosimetry with polymer gels—a TLD reference system. (11th February 2019) - Mann, P; Schwahofer, A; Karger, C P
Abstract: Background and purpose . Absolute dosimetry in 3D with polymer gels (PG) is generally complicated and usually requires a second independent measurement with conventional detectors. This is why, PG are often used only for relative dosimetry. To overcome this drawback, we combine PG with a 1D thermoluminescence (TL) detector within the same measurement. The TL detector information is then used as additional information for calibration of the gel. Materials and methods . The PAGAT dosimetry gel was used in combination with TLD600 (LiF:Mg, Ti). TL detectors were attached on the surface of the PG container placed inside a cylindrical phantom. To test the usability of this setup, two irradiation geometries were carried out: (a) homogeneous target coverage and (b) small-field irradiation. PG was evaluated with magnetic resonance imaging (MRI) and the TL detectors with a Harshaw 5500 hot gas reader. Results . PG dosimetry alone showed deviations of up to 4% as compared to calculations. Including additionally the dose information of the TL detectors for PG calibration, this deviation was decreased to less than 1% for both irradiation geometries. This is also reflected by the very high -passing rates of > 96% (3%/3 mm) and >93% (2%/2 mm), respectively. Conclusion . This study presents a novel method combining 3D PG and TL dose measurements for the purpose of absolute 3D dose measurements that can also be applied in complex anthropomorphic phantoms using only a single measurement. The method was validated for two different irradiation geometries including a homogeneous large field as well as a small field irradiation with sharp dose gradients.